Isolation of non-heparin-binding and heparin-binding proteins of boar prostate - Manásková, Pavla; Liberda, Jirí; Tichá, Marie; Jonáková, Vera (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2002)
Proteins of boar prostate secretion were separated by affinity chromatography on heparin-polyacrylamide to non-heparin-binding (H) and heparin-binding (H+) protein fractions. H- and H+ fractions were then subjected to RP HPLC. Elution profiles of H-and H+ fractions of prostate secretion were compared with those of seminal plasma and the amounts of corresponding proteins were compared. Besides, the isolated proteins were characterized by SDS-PAGE. In the H- fraction of prostate secretion, PSP I and PSP II spermadhesins and in the H+ fraction AQN 2 and AWN 1 spermadhesins were found in substantially lower amounts than in seminal plasma. On the contrary, beta-microseminoprotein was identified in abundant amounts both in H- and H+ fractions of boar prostate secretion. AQN 2 and AWN 1 spermadhesins were proved by their antibodies. Some seminal plasma proteins originating mainly in seminal vesicles could also be secreted by the prostatic gland. beta-Microseminoprotein was found to be produced mainly by the prostate.
Keywords: kationické antimikrobiální peptidy; Electrophoresis, Polyacrylamide Gel; Chromatography, High Pressure Liquid; prostata; elektroforéza v polyakrylamidovém gelu; krevní proteiny; chromatografie afinitní; zvířata; heparin; Antimicrobial Cationic Peptides; transportní proteiny; Chromatography, Affinity; Swine; Carrier Proteins; Blood Proteins; Heparin; Male; Prostate; Animals; mužské pohlaví; vysokoúčinná kapalinová chromatografie; prasata